Distribution of persistent organic pollutants in serum, omental, and parietal adipose tissue of French women with deep infiltrating endometriosis and circulating versus stored ratio as new marker of exposure. (December 2016) - Ploteau, Stéphane; Antignac, Jean-Philippe; Volteau, Christelle; Marchand, Philippe; Vénisseau, Anaïs; Vacher, Vincent; Le Bizec, Bruno
Abstract: Several studies have assessed the potential role of environmental chemicals in the onset, growth, and/or physiopathology of endometriosis. However, their contour in terms of considered exposure markers remains limited. The present study aimed to characterize the internal exposure levels of 78 persistent organic pollutants (POPs, including dioxins, polychlorobiphenyls, brominated flame retardants and organochlorine pesticides) in a set of 113 adult French women (45 controls, 68 cases), and to characterize the distribution of these POPs within three biological compartments (omental adipose tissue, parietal adipose tissue, and serum). For all targeted substances, the correlation between the concentrations measured in omental versus parietal adipose tissue was found strongly significant (p < 0.0001). An equivalence of the measures performed in parietal and omental adipose tissue was moreover observed with median levels of 6.4 vs. 7.4 pg/g l.w. for WHO-TEQ2005 PCDD/F, 4.5 vs. 4.7 pg/g l.w. for WHO-TEQ2005 dl-PCB, 137.1 vs. 147.9 ng/g l.w. for sum of 6 ndl-PCB, and 2.1 vs. 2.0 ng/g l.w. for sum of 7 i-PBDE, respectively. The same observation was made for individual targeted OCs compounds. Significant correlations were also observed between these concentrations determined in adipose tissue and those measured in serum for dioxins (WHO-TEQ2005 PCDD/F = 6.1 pg/g l.w), PCBs (WHO-TEQ2005 dl-PCB = 3.6 pg/g l.w., sum of 6 ndl-PCB = 81.1 ng/g l.w.), and brominated flame-retardants (sum of 7 i-PBDE = 0.9 ng/g l.w.). The circulating versus stored ratio of some exposure markers (Sum PCDDs, 1, 2, 3, 6, 7, 8-HxCDF, slightly versus highly chlorinated PCBs ratio, PBDE 99 and PBB 153) was found statistically different for control and case individuals. These extended exposure data from deep infiltrating endometriosis patients are the first ones available for France and give a new insight about the equilibrium of chemicals between storage and circulating compartments that should be further considered as new marker of exposure in the context of exposure-health relationship studies. Highlights: Internal exposure levels of 78 POPs determined in a set of 113 French women Distribution of these POPs established in parietal and omental fat, and serum Significant correlations observed within the three biological compartments Storage versus circulating ratio appears as a new exposure marker of interest.